2022
DOI: 10.3390/su14137775
|View full text |Cite
|
Sign up to set email alerts
|

Continuance Usage Intention toward E-Payment during the COVID-19 Pandemic from the Financial Sustainable Development Perspective Using Perceived Usefulness and Electronic Word of Mouth as Mediators

Abstract: Digital transformation is essential to financial sustainable development. Since the beginning of 2020, the whole world has been under the influence of the COVID-19 pandemic, which has accelerated the pace of financial digitization. According to the perceived usefulness of the technology acceptance model (TAM) and the perceived seriousness of the health belief model (HBM), this study developed and explored the theoretical framework of consumers’ continuance usage intention toward e-payment. A questionnaire surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Previous research fromChaveesuk et al (2022),Liu et al (2022), andRawashdeh et al (2021) confirmed that perceived usefulness does not influence the intention of continuity of use.While H8 is accepted, satisfaction significantly affects continuity intentions with tstatistic results of 6.006 and a p-value of 0.000. It shows that user satisfaction with digital…”
mentioning
confidence: 85%
“…Previous research fromChaveesuk et al (2022),Liu et al (2022), andRawashdeh et al (2021) confirmed that perceived usefulness does not influence the intention of continuity of use.While H8 is accepted, satisfaction significantly affects continuity intentions with tstatistic results of 6.006 and a p-value of 0.000. It shows that user satisfaction with digital…”
mentioning
confidence: 85%
“…Roy et al ( 2017 ) also found that the platform's fintech application increased user satisfaction and WOM in the retail industry. Similarly, Liu et al ( 2022 ) found that electronic payment services, one of the significant fintech, could increase the perceived usefulness and payment efficiency of users, thereby increasing the WOM of financial platforms. On the other hand, existing research has explored the driving influence factors in the process of fintech's influence on WOM.…”
Section: Introductionmentioning
confidence: 95%
“…This component explains how personal and environmental factors interact to predict individual action. In prior research within the realm of technology adoption, scholarly inquiries commonly integrate various behavioral intentions, encompassing aspects such as word-ofmouth intention, e.g., [59][60][61], online purchase intention, e.g., [62], or continuance usage intention, e.g., [59]. Consequently, behavioral intention can be categorized as the degree of an individual's anticipation to execute a certain action [26,63].…”
Section: M-payment Intentionmentioning
confidence: 99%
“…The surplus of benefits over costs is integral to shaping the overall perceived value [47]. While other studies have explored the impact of perceived benefits and costs on behavioral intention [59,60], this study specifically focuses on examining perceived value. Within this concept, consumers have meticulously evaluated the benefits in relation to the sacrifices.…”
Section: M-payment Intentionmentioning
confidence: 99%
See 1 more Smart Citation